CPU86017, a berberine derivative, attenuates cardiac failure through normalizing calcium leakage and downregulated phospholamban and exerting antioxidant activity - Qi Min-you; Feng Yu; Dai De-zai; Li Na; Cheng Yu-si; Dai Yin (Acta Pharmacologica Sinica, 2016)
Aim: To investigate whether CPU86017, a berberine derivative, attenuates heart failure by blocking calcium influx and exerting its antioxidant activity. Methods: Myocardial infarction was induced in male Sprague-Dawley rats for 17 d followed by isoproterenol (ISO) (5 mg/kg, sc) treatment for 5 d to reduce cardiac function. The rats were divided into 5 groups: sham operation, myocardial infarction (MI), MI plus ISO, and co-treated (in mg/kg, po) with either propranolol (PRO, 10) or CPU86017 (80). Hemodynamic measurements were conducted, and measurements of the redox system, calcium handling proteins and endothelin (ET) system in vivo were done. Furthermore, calcium flux studies and PLB immunocytochemistry were conducted in vitro. Results: Compared to sham operation, HF was evident following MI and further worsened by ISO treatment. This occurred in parallel with downregulated mRNA and protein production of SERCA2a, PLB, and FKBP12.6, and was associated with upregulation of preproET-1, endothelin converting enzyme, and PKA mRNA production in the myocardium in vivo. Calcium leakage was induced by ISO treatment of isolated beating myocytes in vitro. These changes were attenuated by treatment with either PRO or CPU86017. PLB fluorescence in myocytes was downregulated by ISO treatment, and was relieved significantly by treatment with antioxidant aminoguanidine, ascorbic acid or CPU86017 in vitro. Conclusion: HF, calcium leakage, downregulated PLB, FKBP12.6, SERCA2a production, and upregulated PKA were caused by ISO treatment, and were abolished by CPU86017 treatment. The beneficial effects of CPU86017 are attributable to its antioxidant and calcium influx blocking effects.